Mental workload investigation among employees in a selected oil and gas company / Christyne Surindai C. Moosom - Christyne Surindai, C. Moosom (2020)
In recent years, there has been a substantial amount of studies being conducted in mental workload and mental health but there is little research conducted in the Malaysian context especially in the oil and gas field. This gives rise to the need for researching the level of mental workload and mental health problems that will help the stakeholders to protect the wellbeing of their employees. This study aims to investigate the mental workload and level of depression, anxiety and stress scale of employees in a selected oil and gas company by using CarMen-Q and DASS-21 mental health assessment tools, finds the correlation between these parameters and propose recommendations to the company to improve the mental health of their employees. The mental workload statistical analysis revealed that the employees were highly burdened in performance demands (M=76.60) followed by cognitive demands (M=65.65), temporal demands (M=57.34) and emotional demands (M=48.78). 48.98% of employees were determined to have a normal score of depression., 63.27% has a normal score of stress and 18 (36.74%) has a normal score of anxiety. Significant findings reported that 12.24% have extremely severe depression and anxiety and 4.08% worker found to be extremely severe stressful working in the company. The level of depression, anxiety, stress and mental workload of the employees have significant correlations with each other of at least r=0.453. These findings have tailored the researcher to develop strategies for the company to curb mental health problems arising in the company based on the condition and nature of the business activities of the company.